Modified Water Diversion Structures Can Behaviorally Deter Juvenile Chinook Salmon from Entrainment. Issue 5 (17th August 2015) - Mussen, Timothy D.; Cocherell, Dennis E.; Patton, Oliver; Jauregui, Denisse; Ercan, Ali; Bandeh, Hossein; Meier, Dan; Thomas, Steve; Kavvas, M. Levent; Cech, Joseph J.; Fangue, Nann A.
Abstract: Juvenile Chinook Salmon Oncorhynchus tshawytscha traveling in river systems can become entrained by unscreened water diversions when they encounter inflow velocities that exceed their avoidance (i.e., swimming) ability. We tested the efficiency of three devices for deterring fish entrainment; the devices reduced the diversion's maximum inflow velocity by dispersing the inflow across a greater area so as to reduce fish entrainment without causing a decrease in water diversion rates. Tests were performed in a river simulation flume at a 0.15‐m/s sweeping velocity in clear water conditions during the daytime and nighttime as well as in turbid water (daytime) conditions. Water was diverted at a rate of 0.57 m 3 /s through a 0.46‐m‐diameter pipe. The tested devices included (1) a widened box inlet (1.7 m long × 0.76 m wide × 0.76 m deep) with a trash rack mounted at its entrance (trash rack box), (2) a widened box inlet with a louver array mounted at the entrance (louver box), and (3) a 0.91‐m‐diameter cylinder perforated with 300 evenly spaced, 5‐cm‐diameter holes (perforated cylinder). During 2‐h experiments under daytime conditions, 51.5 of 80 fish (on average) were entrained into the pipe when no device was used (i.e., control), and a fish's mean risk of becoming entrained when passing the pipe once was 14%. The mean entrainment risk during a single pipe passage event was reduced to 7% in the trash rack box treatment (i.e., 50% of the control value), 0.17% in the louver box treatment, and 0.20% in the perforated cylinder treatment. In comparison with the control, the mean number of entrained fish was reduced by 50% in the trash rack box treatment, by 97% in the louver box treatment, and by 93% in the perforated cylinder treatment. These devices also reduced the number of fish that were entrained during darkness or turbid daytime conditions. Our findings suggest that behavioral deterrence devices offer effective, low‐cost alternatives to positive barrier fish screens by protecting juvenile Chinook Salmon from entrainment at water diversion pipes without reducing water pumping efficiency.